BIOEKOLOGI Nerita costata (GASTROPODA) IN MANGROVE REGION KUALA KAMPAR DISTRICT DISTRICT INVITATION OF RIAU PROVINCE - M. Hambali M. Hambali; Sofyan Husein Sireger; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The study was conducted in March 2018. Sampling was conducted in the territorial waters of Kuala Kampar Sub-district, Pelalawan District. The purpose of this research is to know the ecology of N.costata, covering environmental condition, organic matter, population density, frequency of size and relationship of organic matter content in mangrove forest of Kuala Kampar Subdistrict. The method used in this research is survey method. The sampling station is determined purposively, by considering the condition of the sampling region. Each station has 3 transects and each transect consists of 3 plots so that there are 9 stations plot. Based on the research result, it can be concluded that Kuala Kampar water environment condition is still good, the highest organic material is at station II that is 14,89% and the lowest is at station I that is 6,77%. Population density between stations and between zones in Kuala Kampar Sub-district on N. costata ranges ranges up to 4.33-8.67 ind / m2. The class-size distribution of this dominating species found in the study sites was a size class (2.1-3.0 cm). The effect of organic content of sediment with N. costata density in research area was moderate with correlation coefficient value (r) = 0,30. Keywords: Density, N. costata, Organic Sediment